Evaluasi Keamanan Sistem Informasi Menggunakan Fuzzy FMEA Berbasis Framework ISO/IEC 27001:2013 untuk Meningkatkan Keamanan Informasi - Kusnandar, Aris (Diponegoro University, 2024)
Very few organizations are not aware of the importance of information security, even though information security is important to the running of an organization. Dinas Kependudukan XYZ faces a number of information security threats from various sources. Every security threat such as information theft, fraud, vandalism, and computer hacking will affect the organization. This research uses the ISO/IEC 27001:2013 framework as a method for. analyze risks. The risk value calculation uses the FMEA method which is integrated with the fuzzy method to determine the risk level of information security threats based on ISO/IEC 27001:2013. The research results are in the form of a risk processing report containing a list of risk priorities and control plans according to the ISO/IEC 27001:2013 standard. The information security risk priorities obtained in this research were 13 very high priority and 10 high priority. This proves that the organization has not complied with standard security/information procedures so it needs to document security policies based on ISO/IEC 27001:2013 to provide a sense of security and increase trust in the public.